Ανάπτυξη μηχανισμού διαχείρισης σκόνης για μηχανή SLS/SLM - Ψαρομμάτης-Γιαννακόπουλος, Φοίβος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών, 2016)
The landscape of additive manufacturing has changed dramatically over the last years especially with 3D printing technologies. Nowadays, 3D printing technologies are increasingly used either for manufacturing or for personal use. Selective Laser Sintering or Selective Laser Melting (SLS/SLM) is a prominent example of high accuracy Additive Manufacturing variants. The material is in the form of fine powder which is deposited as a thin layer on a surface, then it is compacted appropriately; finally, a high power laser scans the surface, sintering/melting the powder locally; non-processed areas remain to support the subsequent layers and in this way a complex three-dimensional shape can be produced layer by layer according to the CAD model. The current work aimed to design and manufacture an efficient mechanism for powder management for an SLS/SLM machine that is being developed at NTUA’s Manufacturing Technology Lab. This part of the machine is critical because it critically influences the accuracy of the part to be produced as well as the speed of production. The system is composed of different sub-systems, the mechanism that is depositing powder to the working table, the mechanism that levels up the powder and the structure that seals the working area from powder leaking. The design phase had two stages, namely conceptualization of the various mechanisms and their detailed design. During the conceptualization stage numerous alternative designs were produced. Using the Analytic Hierarchy Process (AHP) the alternatives were evaluated based on user defined criteria and the most suitable alternative was selected. The latter was detail-designed using a commercial CAD software package to a point that made it ready for manufacturing. Finalization of the design included selection of the electronics for driving motors and managing sensors. The next step in the development process was the manufacturing of the components on CNC machines, based on G-code generated using a commercial CAM software package. Thereafter, assembly took place. The machine was tested in two phases. The first test was without powder and aimed to check proper operation of the electronics as well as their integration with the existing electronics of the other systems of the machine. The second phase was a full scale testing of the developed mechanism with polymer powder during the layer building procedure. In this stage, the weaknesses of the machine were noted and categorized into compulsory actions before the mechanical calibration and those that are mere improvements. A calibration plan for the machine utilizing the Taguchi methodology is also proposed.